Hubungan Antara Usia, Beban Kerja dan Status Kepegawaian dengan Kejadian Stres Kerja Pada Pegawai di Pengadilan Agama Mataram - Lalu Arya Primandita; Iing Iing; Lalu Yogi Prasetio Imam; Sulatun Hidayati (Universitas Malahayati Lampung, 2026)
ABSTRACT Work-related stress is a psychological problem commonly experienced by employees and can affect health and work productivity. Work-related stress is influenced by several factors, including age, workload, and employment status. The Objective is to determine the relationship between age, workload, and employment status with the incidence of work-related stress among employees at the Mataram Religious Court. This study was a quantitative observational study with a cross-sectional design. The sampling technique used was total sampling, involving 75 employees as respondents. Data were analyzed using univariate and bivariate analyses, including Spearman correlation and Chi-square tests, with a significance level of p 0.05. The results showed that most respondents were aged ≥ 35 years (64%), had civil servant (ASN) employment status (80%), had a high workload (57.3%), and experienced severe work-related stress (57.3%). Bivariate analysis revealed a significant relationship between age and work-related stress (p = 0.007), between workload and work-related stress (p = 0.034), and between employment status and work-related stress (p = 0.033).Conclusion: There is a significant relationship between age, workload, and employment status with the incidence of work-related stress among employees at the Mataram Religious Court. Keywords: Work-Related Stress, Age, Workload, Employment Status. ABSTRAK Stres kerja merupakan masalah psikologis yang sering dialami oleh pegawai dan dapat berdampak pada kesehatan serta produktivitas kerja. Stres kerja dipengaruhi oleh berbagai faktor, di antaranya usia, beban kerja, dan status kepegawaian. Tujuan penelitian untuk mengetahui hubungan antara usia, beban kerja, dan status kepegawaian dengan kejadian stres kerja pada pegawai di Pengadilan Agama Mataram. Penelitian ini adalah penelitian kuantitatif observasional dengan desain cross sectional. Teknik pengambilan sampel menggunakan total sampling dengan jumlah responden sebanyak 75 pegawai. Analisis data dilakukan secara univariat dan bivariat menggunakan uji korelasi Spearman dan uji Chi-square dengan tingkat signifikansi p 0,05. Hasil penelitian menunjukkan bahwa sebagian besar responden berusia ≥ 35 tahun (64%), berstatus ASN (80%), memiliki beban kerja tinggi (57,3%), dan mengalami stres kerja berat (57,3%). Hasil analisis bivariat menunjukkan terdapat hubungan yang signifikan antara usia dengan stres kerja (p = 0,007), terdapat hubungan yang signifikan antara beban kerja dengan stres kerja (p = 0,034), serta terdapat hubungan yang signifikan antara status kepegawaian dengan stres kerja (p = 0,033). Terdapat hubungan yang signifikan antara usia, beban kerja, dan status kepegawaian dengan kejadian stres kerja pada pegawai di Pengadilan Agama Mataram. Kata Kunci: Stres Kerja, Usia, Beban Kerja, Status Kepegawaian.